Immunogenicity and in vivo efficacy of recombinant Plasmodium falciparum merozoite surface protein-1 in Aotus monkeys. - Kumar, S. (The Feinstein Institute for Medical Research, 1995)
BACKGROUND: The carboxy-terminus of the merozoite surface protein-1 (MSP1) of Plasmodium falciparum has been implicated as a target of protective immunity. MATERIALS AND METHODS: Two recombinant proteins from the carboxy-terminus of MSP1, the 42 kD fused to GST (bMSP1(42)) and the 19 kD (yMSP1(19)), were expressed in Escherichia coli and secreted from Saccharomyces cerevisiae, respectively. To determine if vaccination with these recombinant proteins induces protective immunity, we conducted a randomized, blinded vaccine trial in two species of Aotus monkeys, A. nancymai and A. vociferans. After three injections using Freund's adjuvant, the monkeys were challenged with the virulent Vietnam Oak Knoll (FVO) strain of P. falciparum. RESULTS: All three control monkeys required treatment by Day 19. Two of three monkeys vaccinated with bMSP1(42) required treatment by Day 17, whereas the third monkey controlled parasitemia for 28 days before requiring treatment. In contrast, both of the A. nancymai vaccinated with yMSP1(19) self-resolved an otherwise lethal infection. One of the two yMSP1(19)-vaccinated A. vociferans had a prolonged prepatent period of > 28 days before requiring treatment. No evidence of mutations were evident in the parasites recovered after the prolonged prepatent period. Sera from the two A. nancymai that self-cured had no detectable effect on in vitro invasion. CONCLUSIONS: Vaccination of A. nancymai with yMSP1(19) induced protective immune responses. The course of recrudescing parasitemias in protected monkeys suggested that immunity is not mediated by antibodies that block invasion. Our data indicate that vaccine trials with the highly adapted FVO strain of P. falciparum can be tested in A. nancymai and that MSP1(19) is a promising anti-blood-stage vaccine for human trials.